Aircraft system safety : military and civil aeronautical applications - Kritzinger, Duane; ScienceDirect eBooks (Cambridge, England : Woodhead Pub. ; Boca Raton : CRC Press, 2006)
Demonstrating safety for the application of ever increasingly complex technologies is always a formidable task. In the event of an accident society want someone to blame. How would your records face up to legal scrutiny and how would you be able to demonstrate that you have taken reasonable care as a professional engineer/manager should you be faced with a court appearance? The problem is that many system engineers do not have the appropriate training; the required safety approaches, tools and techniques; and their managers do not know when and how they may be applied and appropriately resourced. This book aims to provide a basic skill-set for both safety practitioners and their managers by defining stakeholder (civil, military and legal) expectations and showing how these expectations can be efficiently accomplished and managed throughout the product lifecycle (i.e from concept design to product disposal).
Introduction -- Safety within the legal framework -- The safety concept -- Standards and regulations -- Risk-based approach -- Goal-based approach -- Hazards -- The fail-safe dimension -- The system safety assessment -- The safety case -- Numerical probabilistic approach -- Minimum equipment lists -- The safety management system -- Concluding observations -- Safety assessment tools and techniques -- Safety criteria -- GSN safety argument.
Includes bibliographical references (pages 335-338) and index.
Elsevier
Keywords: Aeronautics -- Safety measures; Airplanes -- Design and construction; TRANSPORTATION -- Aviation -- General; Aeronautics -- Safety measures; Airplanes -- Design and construction; Electronic books